Tantangan Masyarakat Adat Baduy Banten Kidul Terhadap Perubahan Sosial Budaya - Robby Nurtresna; Dika Ratu Marfu’atun; Muhamad Yusar (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
The Kasepuhan adat community of Banten Kidul in Sirnaresmi Village is a traditional society that still adheres to the heritage of their ancestors. Along with the development of incoming science and technology, the Kasepuhan community is gradually experiencing cultural changes. The cultural changes that occur as a result of the challenges and responses of the indigenous Kasepuhan community to new things have resulted in cultural acculturation. The purpose of this study is to determine changes in the culture of the indigenous people of Banten Kidul. This research method uses historical research methods. Historical research is a process of reconstructing history by collecting historical facts and data, then building them into a single unit. The results of this study show that this cultural change is due to the challenges of an increasingly ultramodern era and the response of society to new things so that cultural acculturation occurs. This change is evidenced by elements of several cultures such as technological systems, belief systems and changing language speech. But thus, even though not every change becomes negative, it means that there can also be positive changes that occur in the Kasepuhan indigenous people of Banten Kidul.